Some exact results for the zero-bandwidth extended Hubbard model with intersite charge and magnetic interactions - Kapcia, Konrad Jerzy; Kłobus, Waldemar; Robaszkiewicz, Stanisław (Polish Academy of Sciences, Institute of Physics, al. Lotników 32-46, PL-02-668 Warsaw, Poland, 2015)
The extended Hubbard model in the zero-bandwidth limit is studied. The effective Hamiltonian consists of (i) on-site U interaction and intersite (ii) density-density interaction W and (iii) Ising-like magnetic exchange interaction J (between the nearest-neighbors). We present rigorous (and analytical) results obtained within the transfer-matrix method for 1D-chain in two particular cases: (a) W=0 and n=1; (b) $U\rightarrow+\infty$ and n=1/2 ($W\neq 0$, $J\neq 0$). We obtain the exact formulas for the partition functions which enables to calculate thermodynamic properties such as entropy, specific heat (c), and double occupancy per site. In both cases the system exhibits an interesting temperature dependence of c involving a characteristic two-peak structure. There are no phase transitions at finite temperatures and the only transitions occur in the ground state.
This is an author-created, un-copyedited version of an article accepted for publication in Acta Physica Polonica A.
Keywords: extended Hubbard model; atomic limit; magnetism; charge-order; phase separation; transfer matrix method; 1D-chain